Non-invasive characterization of amyotrophic lateral sclerosis in a hTDP-43(A315T) mouse model: A PET-MR study - Weerasekera, Akila (Neuroimage Clin, 2020)
Currently TAR DNA binding protein 43 (TDP-43) pathology, underlying Amyotrophic Lateral Sclerosis (ALS), remains poorly understood which hinders both clinical diagnosis and drug discovery efforts. To better comprehend the disease pathophysiology, positron emission tomography (PET) and multi-parametric magnetic resonance imaging (mp-MRI) provide a non-invasive mode to investigate molecular, structural, and neurochemical abnormalities in vivo. For the first time, we report the findings of a longitudinal PET-MR study in the TDP-43(A315T) ALS mouse model, investigating disease-related changes in the mouse brain. 2-deoxy-2-[(18)F]fluoro-D-glucose [(18)F]FDG PET showed significantly lowered glucose metabolism in the motor and somatosensory cortices of TDP-43(A315T) mice whereas metabolism was elevated in the region covering the bilateral substantia nigra, reticular and amygdaloid nucleus between 3 and 7 months of age, as compared to non-transgenic controls. MR spectroscopy data showed significant changes in glutamate + glutamine (Glx) and choline levels in the motor cortex and hindbrain of TDP-43(A315T) mice compared to controls. Cerebral blood flow (CBF) measurements, using an arterial spin labelling approach, showed no significant age- or group-dependent changes in brain perfusion. Diffusion MRI indices demonstrated transient changes in different motor areas of the brain in TDP-43(A315T) mice around 14 months of age. Cytoplasmic TDP-43 proteinaceous inclusions were observed in the brains of symptomatic, 18-month-old mice, but not in non-symptomatic transgenic or wild-type mice. Our results reveal that disease- and age-related functional and neurochemical alterations, together with limited structural changes, occur in specific brain regions of transgenic TDP-43(A315T) mice, as compared to their healthy counterparts. Altogether these findings shed new light on TDP-43(A315T) disease pathogenesis and may prove useful for clinical management of ALS.